2020
DOI: 10.1002/term.3101
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative effects of human chondrocyte sheets in a xenogeneic transplantation model using immune‐deficient rats

Abstract: Although cell transplantation has attracted much attention in regenerative medicine, animal models continue to be used in translational research to evaluate safety and efficacy because cell sources and transplantation modalities are so diverse. In the present study, we investigated the regenerative effects of human chondrocyte sheets on articular cartilage in a xenogeneic transplantation model using immune‐deficient rats. Osteochondral defects were created in the knee joints of immune‐deficient rats that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Nowadays, increasing number of patients who damage their articular cartilage because of aging, trauma or degenerative disease have greatly affected their life quantity and create a huge social burden (Makris, Gomoll, Malizos, Hu, & Athanasiou, 2015; Patel, Saleh, Burdick, & Mauck, 2019). Current strategies for repairing cartilage defects including microfracture, tissue debridement, and autologous or allogeneic cartilage transplantation have been developed, but severe limitations of them have been reported as well, such as inferior biomechanical property of the repaired region and limited appropriate cartilage donor tissue (Armiento, Alini, & Stoddart, 2019; Y. Liu, Zhou, & Cao, 2017; Takizawa et al., 2020). Cartilage tissue engineering (CTE) that combines biodegradable scaffolds, cells and biologically active molecules has been proved as a promising tool for repairing cartilage defects in both experimental models and clinical patients (Deng et al., 2019; Kwon et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, increasing number of patients who damage their articular cartilage because of aging, trauma or degenerative disease have greatly affected their life quantity and create a huge social burden (Makris, Gomoll, Malizos, Hu, & Athanasiou, 2015; Patel, Saleh, Burdick, & Mauck, 2019). Current strategies for repairing cartilage defects including microfracture, tissue debridement, and autologous or allogeneic cartilage transplantation have been developed, but severe limitations of them have been reported as well, such as inferior biomechanical property of the repaired region and limited appropriate cartilage donor tissue (Armiento, Alini, & Stoddart, 2019; Y. Liu, Zhou, & Cao, 2017; Takizawa et al., 2020). Cartilage tissue engineering (CTE) that combines biodegradable scaffolds, cells and biologically active molecules has been proved as a promising tool for repairing cartilage defects in both experimental models and clinical patients (Deng et al., 2019; Kwon et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In conducting clinical studies on the transplantation of autologous chondrocyte sheets [ 20 ] and polydactyly-derived chondrocyte sheets for articular cartilage regeneration, we have reported the characteristics and therapeutic effects of both types of sheet in animal experiments using mini-pigs, rabbits, and rats [ 22 , 23 , 24 , 25 ]. Our previous flow cytometric analysis studies have shown that PD sheets express MSC markers and our histological analyses have shown that PD sheets are multiply stratified without stacking, as in autologous chondrocyte sheets [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cell sheet technology employing chondrocyte sources has shown preliminary success in both pre-clinical models and small cohort clinical studies [ 24 , 25 , 173 , 175 , 176 , 177 , 180 , 181 , 182 , 183 , 184 ]. Chondrocyte sheets adhere directly and spontaneously to cartilage tissue via retained endogenous ECM and adhesion proteins.…”
Section: Cell Sheet Technology As a Transplantable 3d Tissue-like mentioning
confidence: 99%
“…Notably, this strength of defect site adhesion for the undifferentiated chondrocyte sheets is sufficient to allow initial defect retention without suturing, and to withstand knee joint mechanical forces while maintaining long-term localization of transplanted cells [ 24 , 173 , 177 , 180 , 182 , 185 ]. This engraftment capability facilitates successful chondrocyte sheet induction of hyaline-like cartilage regeneration in articular cartilage focal chondral defects by 4 weeks post-transplantation [ 24 , 25 , 173 , 177 , 180 , 181 , 182 ] ( Figure 4 a–d).…”
Section: Cell Sheet Technology As a Transplantable 3d Tissue-like mentioning
confidence: 99%